The first records of Mesocapnia (Plecoptera: Capniidae) from China with description of a new species - Chen, Zhi-Teng; Du, Yu-Zhou (Zootaxa, 2016)
Three species of the capniid genus Mesocapnia are reported from the Inner Mongolia Autonomous Region of China, M. variabilis and M. gorodkovi, and M. daxingana sp. nov. These are the first records for the genus from China, extending the distribution of Mesocapnia into the Inner Mongolia Autonomous Region.